The Development of The Education System at Karshi State University During The Years of Independence - Muminova Gavhar Esonovna; Shadiyeva Dilnoza Aminovna (Pubmedia Social Sciences and Humanities, 2025)
This article analyzes the impact of educational reforms implemented in Uzbekistan during the years of independence on the activities of Karshi State University. Based on the laws and decrees adopted in 1992, 1997, and 2020, the paper examines the restructuring of faculties, centers, and departments, the introduction of a two-tier education system, and the implementation of admission through testing. The role of social and humanitarian sciences in the educational process of the university is also emphasized.